Reconfigurable dynamic all-optical chaotic logic operations in an optically injected VCSEL - 钟东洲;许葛亮;罗伟;肖珍珍 (Chinese physics B, 2017)
In a chaotic system of vertical cavity surface emitting laser （VCSEL） with external optical-injection, we propose a novel implementation scheme for reconfigurable dynamic all-optical chaotic logic operations （AOCLOs）. Under different key parameters, such as the bias current, the injection strength and the frequency detuning of the injected light field and the VCSEL, we also explore the evolutions of the polarization-bistability with the amplitude of the injected light field when the output of VCSEL is chaotic wave. According to the dynamic evolutions, we find out the optimal value of the frequency detuning that is considered as a control logic signal, and further implement different AOCLOs, such as AND, NAND, OR, NOR, XOR, and XNOR, by controlling the logic operation of the control logic signal between two logic inputs. Moreover, the ability to reconstruct these logic operations is demonstrated under relatively low noise strength of the spontaneous emission.